2018
DOI: 10.1175/bams-d-16-0221.1
|View full text |Cite
|
Sign up to set email alerts
|

Building the Sun4Cast System: Improvements in Solar Power Forecasting

Abstract: As integration of solar power into the national electric grid rapidly increases, it becomes imperative to improve forecasting of this highly variable renewable resource. Thus, a team of researchers from the public, private, and academic sectors partnered to develop and assess a new solar power forecasting system, Sun4Cast. The partnership focused on improving decision-making for utilities and independent system operators, ultimately resulting in improved grid stability and cost savings for consumers. The proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…W-E-F Nexus-related information projects include the Vision on Technology for a Better World, a system that facilitates data processing and distribution and analyzes global trends affecting the W-E-F Nexus (https://vito.be/en), and the GIZ Water, Energy & Food Security Resource Platform (http://www.water-energyfood.org/). An example for the energy sector is a system being developed by Haupt et al (2018) to forecast solar energy outputs. The water sector is covered by the Aqueduct system, developed by the Water Resources Institute, which has more than a decade of experience in shaping outputs for those needing water risk assessment tools (http://aqueduct.wri.org).…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…W-E-F Nexus-related information projects include the Vision on Technology for a Better World, a system that facilitates data processing and distribution and analyzes global trends affecting the W-E-F Nexus (https://vito.be/en), and the GIZ Water, Energy & Food Security Resource Platform (http://www.water-energyfood.org/). An example for the energy sector is a system being developed by Haupt et al (2018) to forecast solar energy outputs. The water sector is covered by the Aqueduct system, developed by the Water Resources Institute, which has more than a decade of experience in shaping outputs for those needing water risk assessment tools (http://aqueduct.wri.org).…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…These improvements have stemmed from including observations in the immediate vicinity of the resource, both in the nowcasting and assimilated into the NWP models, as well as better methods of blending multiple models for the appropriate timescales. Solar power predictions have not been a focus for very long, but rapid improvement is also happening here (Lorenz et al 2009;2014;Tuohy et al 2015;Haupt et al 2017).…”
Section: Probabilistic Forecasts and The Analog Ensemblementioning
confidence: 99%
“…All these changes have been incorporated in a specific augmentation of the advanced research version of the WRF Model [35] designed for solar energy predictions known as WRF-Solar [36]. WRF-Solar has been extensively tested in the USA [36][37][38][39][40][41] and other countries, such as Spain [42], Singapore [43], Kuwait [44], and Saudi Arabia [45]. Most studies have reported significant improvements in solar irradiance predictions under different sky conditions with WRF-Solar in comparison to standard WRF simulations.…”
Section: Introductionmentioning
confidence: 99%